Status of adjuvant endocrine therapy for breast cancer - Schiavon, Gaia (BioMed Central, 2014)
Adjuvant endocrine therapy reduces the risk of recurrence and death from breast cancer in women with hormone receptor-positive early breast cancer. Tamoxifen has been the standard therapy for decades, and this is still the case for pre-menopausal women. Ovarian suppression is of similar efficacy but currently there is no strong evidence for adding this to tamoxifen and the additional morbidity can be considerable. Results from two important trials addressing this issue are imminent. In post-menopausal women, aromatase inhibitors (AIs) (letrozole, anastrozole, or exemestane) are superior to tamoxifen in preventing recurrence but only letrozole has been shown to improve survival. The main gain is against high-risk cancers, and tamoxifen gives very similar benefit for low-risk disease. Traditionally, treatment has been given for around 5 years, but many women remain at risk of relapse for 10 years or more. The AIs, and more recently tamoxifen, have been shown to reduce further the risk of late recurrence in women still in remission after 5 years of tamoxifen if given for a further 5 years. The comparative benefits of these two options and the selection of patients most likely to benefit from long-term adjuvant endocrine therapy are important topics for further research, as is the optimum duration of AI therapy started upfront.